Os desigrejados : estudo sobre o fenômeno da desinstitucionalização contemporânea nas igrejas evangélicas - Bilhalva, Alexandre Oliveira (2020)
This work analyzes, from a bibliographic point of view, in the history of Christianity, and in the socio-cultural context, the origins of the religious phenomenon, especially in the evangelical field, popularly known as "Desigrejados". The phenomenon of the disenfranchised arises with the interpretation that every religious structure presents itself as an “unnecessary institution,” arguing that the Christian faith can be exercised without the communion of the church. These ideas are being conveyed through books, lectures and media, becoming a growing movement every day. This decentralization of a church, professing a form of faith beyond the institution, is a new religious understanding, which, although complex and difficult, requires study to understand its motivation and extension